Late Pleistocene Expansion of Small Murid Rodents across the Palearctic in Relation to the Past Environmental Changes - Kozyra, Katarzyna; Zając, Tomasz M; Ansorge, Hermann; Wierzbicki, Heliodor; Moska, Magdalena; Stanko, Michal; Stopka, Pavel (Genes, 2021)
We investigated the evolutionary history of the striped field mouse to identify factors that initiated its past demographic changes and to shed light on the causes of its current genetic structure and trans-Eurasian distribution. We sequenced mitochondrial cyt b from 184 individuals, obtained from 35 sites in central Europe and eastern Mongolia. We compared genetic analyses with previously published historical distribution models and data on environmental and climatic changes. The past demographic changes displayed similar population trends in the case of recently expanded clades C1 and C3, with the glacial (MIS 3-4) expansion and postglacial bottleneck preceding the recent expansion initiated in the late Holocene and were related to environmental changes during the upper Pleistocene and Holocene. The past demographic trends of the eastern Asian clade C3 were correlated with changes in sea level and the formation of new land bridges formed by the exposed sea shelf during the glaciations. These data were supported by reconstructed historical distribution models. The results of our genetic analyses, supported by the reconstruction of the historical spatial distributions of the distinct clades, confirm that over time the local populations mixed as a consequence of environmental and climatic changes resulting from cyclical glaciation and the interglacial period during the Pleistocene.
Keywords: Animals; Geological Phenomena; Climate Change; biomasa; fylogeneze; Phylogeny; DNA, Mitochondrial; zvířata; molekulární evoluce; Biomass; Evolution, Molecular; Animal Distribution; mitochondriální DNA; Muridae; rozšíření zvířat; geologické jevy; klimatické změny